2017
DOI: 10.1177/0266242617740412
|View full text |Cite
|
Sign up to set email alerts
|

How do micro-firms manage coopetition? A study of the wine sector in France

Abstract: Research on coopetition – the simultaneous occurrence of competition and cooperation among firms – is usually limited to the realm of large firms. While some research has examined the motives and outcomes of coopetition among small- and medium-sized business, little is known about how coopetition is managed among micro-firms. The French wine sector is dominated by micro-firms, among which coopetition is common. Focusing on the Pic Saint Loup area in south-eastern France, this article analyses how micro-firms m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(216 citation statements)
references
References 119 publications
6
191
0
4
Order By: Relevance
“…That is, prior theory has indicated that if managers believe that collaborating with their competitors is an important activity (i.e., something that has a positive impact on company performance), then, such individuals are likely to engage in behavioral forms of coopetition (resource and capability-sharing activities) (Brandenburger and Nalebuff, 1996). Further, other authors have stressed that managers must have access to competitors' resources and capabilities for coopetition to exist (Ganesan, Malter and Rindfleisch, 2005;Felzensztein et al, 2012;Granata et al, 2018). While the drivers of coopetition are important to increasing marketing scholars' understanding of how such activities can be best-managed (Gnyawali and Charleton, 2018), this investigation highlights the nature of the coopetition -company performance relationship.…”
Section: Drivers Of Coopetitionmentioning
confidence: 86%
See 3 more Smart Citations
“…That is, prior theory has indicated that if managers believe that collaborating with their competitors is an important activity (i.e., something that has a positive impact on company performance), then, such individuals are likely to engage in behavioral forms of coopetition (resource and capability-sharing activities) (Brandenburger and Nalebuff, 1996). Further, other authors have stressed that managers must have access to competitors' resources and capabilities for coopetition to exist (Ganesan, Malter and Rindfleisch, 2005;Felzensztein et al, 2012;Granata et al, 2018). While the drivers of coopetition are important to increasing marketing scholars' understanding of how such activities can be best-managed (Gnyawali and Charleton, 2018), this investigation highlights the nature of the coopetition -company performance relationship.…”
Section: Drivers Of Coopetitionmentioning
confidence: 86%
“…However, an alternative viewpoint to the above-described research proposition, is that as industry rivalry becomes fiercer, a greater number of rivals could mean that management teams have more opportunities to engage in coopetition (Ganesan et al, 2005;Felzensztein et al, 2018;Mathias et al, 2018). Management teams are more likely to develop performance-driving forms of coopetition if competitors' resources and capabilities can be accessed (Felzensztein et al, 2012;Granata et al, 2018). Furthermore, coopetition activities are effective when organizations are within a close geographic proximity, owing to improving inter-firm relationships (Bengtsson and Kock, 1999;Geldes, Heredia, Felzensztein and Mora, 2017).…”
Section: Competitive Business Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-firms are generally found to be informal in their operations, with business practices that do not strictly follow regulatory procedures (Arrowsmith et al, 2003;Ram et al, 2001;Saridakis, Muñoz Torres and Johnstone, 2013). Crain and Crain, 2010) or excluded (at least some of) them from analysis (Achtenhagen, Ekberg and Melander, 2017;BEIS, 2016b;Blackburn and Hart, 2002;Falk and Hagsten, 2015;Falk et al, 2014;Granata et al, 2018;Hänninen et al, 2017). However, the actual impact of regulation on micro-firms is unclear, since most studies in this area have either tended to consider them to be part of a broad small or small and medium-sized enterprise (SME) segment (e.g.…”
Section: Micro-firms and Regulationmentioning
confidence: 99%